Macromedia Flash animation & cartooning : a creative guide - Fernandez, Ibis. (New York : McGraw-Hill/Osborne, 2002)
A comprehensive guide to Flash animation and cartooning, this book includes an eight-page colour insert which details the stages of the animation process. The tutorial format addresses every facet of character creation and animation, while applied projects illustrate concepts and practices.
PART I: Cartooning and Animation Ch. 1: Introduction to Cartooning Ch. 2: Character Head Ch. 3: Character Body Ch. 4: Character Types Ch. 5: Develop Your Own Characters Ch. 6: The Little Things Ch. 7: Animals Ch. 8: Introduction to Animation Ch. 9: More Animation Ch. 10: Animation Cycles Ch. 11: Animation Technique Ch. 12: Phonetics and Character Vocalization PART II: Macromedia Flash Ch. 13: Introduction to Macromedia Flash Ch. 14: The Flash Interface Ch. 15: Objects Ch. 16: Animation Ch. 17: Movie Management Ch. 18: Sound Ch. 19: Exporting and Publishing Ch. 20: Advanced Actions PART III: The Production Process Ch. 21: Generating Ideas and Concepts Ch. 22: Scripting Ch. 23: Pre-production Ch. 24: Production Ch. 27: Hollywood Technique in Flash Ch. 28: Post Production Ch. 29: Time Saving Tips and Tricks
Includes index.
Keywords: Flash (Computer file); Computer animation; Web sites -- Design